Data Model for Geographic Ontologies Generation - Chaves, Marcirio (2012)
Structured geographic information has an important role in many applications, such as geographically-aware search engines and named-entity (e.g., proper names) recognizers. This information is compiled from resources like dictionaries, gazetteers and ontologies. The quality of the applications depends critically on the richness of these resources. This article describes a new version of the Geographic Knowledge Base (GKB), an environment for integrating geographic data and generating ontologies. We introduce the new metamodel of GKB and show how the information in its repository is transformed into OWL representations. We also present the data integration process of the administrative and physical domains, which deals with geographic relationships in both domains.